Film Coating and Pelleting of Cauliflower Seeds with Molybdenum - Souza, Emanuele Possas de [UNESP]; Bezerra, Sara Raissa de Brito [UNESP]; Sá, Jolinda Mércia de [UNESP]; Ávila, Jorgiani de [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Freitas, Pâmela Gomes Nakada [UNESP] (FapUNIFESP (SciELO), 2025)
Among the most cultivated vegetables, brassicas stand out for their economic and social importance, but they also stand out for their requirement for micronutrients, especially cauliflower. In view of the importance of micronutrients in the development of cauliflower, the objective was to study the effect of treating cauliflower seeds with molybdenum (Mo) through film coating and pelleting techniques on physiological quality and field development and production under different managements. For physiological and seedling quality, twelve treatments were evaluated, in a 2x5+2 factorial scheme: two technologies (film coating and pelleting), five doses (0.5; 1.5; 2.5; 3.5 and 4.5 g of Mo kg-1 of seeds) and two controls (technology without nutrient and untreated seed), with four replications, in a completely randomized design for tests conducted in the laboratory and in randomized blocks for tests in the nursery. For the field, ten treatments were evaluated in a 2x2x2+2 factorial scheme: two seed treatment technologies (film coating and pelleting); two Mo doses (0.5 and 4.5 g kg-1 of seeds), two fertilization managements (as recommended by Trani and coauthors (2022) [4] and fertilization without a Mo source) and two control treatments (untreated seed, one in each management), in a randomized block design, with six replications. The treatment of seeds with Mo did not harm the physiological quality in both film coating and pelleting technologies. However, in the experiment in a protected environment, supplementation with this micronutrient by seeds proved to be unnecessary, as no plants with deficiency symptoms were observed and it did not affect production.
Keywords: Brassica oleracea var. botrytis; emergence; germination; micronutrient; productivity